Pattern of Bone Marrow Involvement by Solid Tumors: Experience from a Tertiary Care Center from South India - Rudresha, AH; Patidar, Rajesh; Lakshmaiah, Kuntegowdanahalli C; Babu, K Govind; Lokanatha, Dasappa; Jacob, Linu Abraham; Babu, MC Suresh; Namrata, NR; Kadabur, N Lokesh; Rajeev, LK; Anand, Abhishek; Asati, Vikas (Indian Journal of Medical and Paediatric Oncology, 2019)
Background: Bone marrow involvement by solid tumor implicates advanced disease and dismal prognosis. Bone marrow aspiration and biopsy are routinely performed as staging workup for certain small round cell tumors and also for unexplained cytopenia in other solid tumors. It is important to rule out bone marrow involvement before planning for curative treatment. Materials and Methods: This was a retrospective observational study. The aim of our study was to evaluate the pattern of bone marrow involvement by different solid tumors and their correlation with the hematological abnormalities. We retrospectively evaluated bone marrow aspirations and biopsy performed in past 3 years. Results: At our institution, bone marrow examinations were performed in 440 patients during past 3 years for solid malignancies. Out of 440, 206 were pediatric cases and 234 were adult cases. Bone marrow was involved in 56 (12.7%) patients. Among the pediatric cases, bone marrow involvement was present in 30 (12.8%) cases, and in adult cases, bone marrow was involved was in 26 (11.1%) cases. Neuroblastoma (40%) was the most common malignancy, which involved the bone marrow among pediatric cases, followed by retinoblastoma (26.6%) and Ewing’s sarcoma (20%). Among adult patients, neuroendocrine carcinoma (23%) was at the top of the list of tumors involving bone marrow, which is followed by Ewing’s sarcoma (19.2%) and nasopharyngeal carcinoma (11.5%). Conclusion: Neuroblastoma and neuroendocrine carcinoma are the major cause of bone marrow involvement among the solid malignancies in pediatric and adult population, respectively. Use of immunohistochemistry markers on bone marrow biopsies may result in higher detection rate.
Keywords: Bone marrow and solid tumor; metastasis to bone marrow; pattern of bone marrow involvement